Design, Synthesis, Characterization, Enzyme Inhibition, Molecular Docking, and Pharmacological Evaluation of New Chalcone-Sulfonate Derivatives Bearing Thiophene - Aslan, Hakan; Yetissin, Fuat; Korkmaz, Adem; Bursal, Ercan (Wiley-V C H Verlag Gmbh, 2024)
The novel chalcone-sulfonate derivatives bearing thiophene motif were synthesized and characterized using 1H NMR, 13C NMR, and HRMS analysis. The evaluation of in vitro and in silico potential pancreatic lipase inhibition activity of the novel chalcone-sulfonate derivatives bearing thiophene motif was scanned. IC50 values of compounds 5 i (28.76 +/- 2.11 mu M) and 5 f (30.58 +/- 0.45 mu M) were determined to be more effective pancreatic lipase inhibitors for in vitro studies. The best potential inhibitor for pancreatic lipase binding affinity was found as compound 5 f (-9.8 kcal mol-1) for in silico studies. Although compounds 5 f and 5 i were identified as the best pancreatic lipase inhibitor candidates in vitro and molecular docking studies, compounds 5 f and 5 i were predicted mutagenic and carcinogenic properties in mice according to ADMET studies. Deeply, compound 5 h was a more effective pancreatic lipase inhibitor according to enzyme inhibition, molecular docking, and ADMET studies. It can be said that compound 5 h may be a more efficient drug candidate than orlistat in the treatment of obesity. This study gives a comprehensive account of the synthesis and assessment of newly developed chalcone-sulfonate derivatives bearing thiophene, specifically providing on their ability to target pancreatic lipase. In summary, our research highlights the potential of chalcone-sulfonate derivatives bearing thiophene as effective enzyme inhibitors that hold promise for therapeutic applications. image
Keywords: Pancreatic lipase; Enzyme inhibition; Thiophene; Chalcone; and Sulfonate derivatives